CEO duality structure and firm performance in Pakistan - Yasser, Qaiser Rafique; Al Mamun, Abdullah; Suriya, Abdul Rahim (Fakulti Ekonomi dan Pengurusan, 2014)
This article examines the impact of CEO duality on firm performance; which attracted much attention, especially in emerging economies, yet yielded several inconsistent empirical results. CEO duality exists when the offices of the CEO and Chairman are retained by the same person. This study examines the relationship between CEO duality and the performance of Pakistani public listed companies by using a sample of five years, from 2007 to 2011. This study tested the hypotheses with data obtained from the Karachi Stock Exchange 100 indexed firms, and employed the agency and stewardship theory perspectives. However, our empirical results do not show a significant relationship between CEO duality and firm performance, but CEO qualification and CEO affiliation are positively associated with firm performance. The results suggest that CEO duality is a less significant issue in corporate governance than suggested by many previous researchers and policy makers. The paper contributes to the literature on corporate governance and firm performance by introducing a framework in identifying and analyzing moderating variables that affect the relationship between CEO duality and firm performance.